2017
DOI: 10.11138/ccmbm/2017.14.3.372
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of nonunion after osteosynthesis of the clavicle: is it a biomechanical or infection problem?

Abstract: SummaryIntroduction. The nonunion rate has been reported between 0.1% and 15%. There are also several predisposing factors for the onset of complications: general factors connected with the patient and specific factors related to the fracture site. The purpose of our study is to review the etiology of nonunion of the clavicle in its atrophic form and investigate the outcomes of the revision treatment in a single step. Materials and methods. Retrospective study on 71 patients suffering from nonunions due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…The purpose of Rollo's study was to review the etiology of nonunion of the clavicle in its atrophic form and investigate the outcomes of the revision treatment in a single step. Rollo also reported that the fibula splint, tricortical bone graft, autologous bone graft and iliac crest bone graft all have mechanical and strong biological values to quickly heal the nonunion. On the other hand all patients treated with ELIN had smooth healing with less complications and more satisfactory results with no revision required for any patient.…”
Section: Discussionmentioning
confidence: 95%
“…The purpose of Rollo's study was to review the etiology of nonunion of the clavicle in its atrophic form and investigate the outcomes of the revision treatment in a single step. Rollo also reported that the fibula splint, tricortical bone graft, autologous bone graft and iliac crest bone graft all have mechanical and strong biological values to quickly heal the nonunion. On the other hand all patients treated with ELIN had smooth healing with less complications and more satisfactory results with no revision required for any patient.…”
Section: Discussionmentioning
confidence: 95%
“…Autologous strut grafting with bone chip augmentation has shown to be a reliable option, with sufficient restoration of length and good functional results, yet has a higher patient morbidity from the donor site. 5,7,8,25 The strut allograft provides more stability than one bridging plate only, and even though it is avascular, it could act as a biological scaffold for bone ingrowth on the anteromedial side which is not possible using a double-plating technique.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes are often unsatisfactory for the patients, as they are associated with long-term morbidity. 7,8 The purpose of our study is to evaluate the outcomes of plateand-bone strut allograft with bone substitute augmentation in the management of aseptic, atrofic non-unions of the humeral shaft.…”
Section: Introductionmentioning
confidence: 99%
“…Neben der stabilen Plattenosteosynthese ist eine interfragmentäre Kompression an den Kontaktflächen vorteilhaft, weshalb wir trapezartig geformte Knochenblöcke bevorzugen. Die ursprüngliche Länge und Form des Schlüsselbeines muss möglichst wiederhergestellt werden [19]. Daher ist eine genaue präoperative Planung unumgänglich, wobei meist die gesunde Gegenseite als Template herangezogen wird.…”
Section: Behandlungunclassified